Coinfection with influenza virus and non-typeable Haemophilus influenzae aggregates inflammatory lung injury and alters gut microbiota in COPD mice - Wu, Xiao; Li, Run-Feng; Lin, Zheng-Shi; Xiao, Chuang; Liu, Bin; Mai, Kai-Lin; Zhou, Hong-Xia; Zeng, De-You; Cheng, Sha; Weng, Yun-Ceng; Zhao, Jin; Chen, Rui-Feng; et al. (Frontiers in Microbiology, 2023)
Background: Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is associated with high mortality rates. Viral and bacterial coinfection is the primary cause of AECOPD. How coinfection with these microbes influences host inflammatory response and the gut microbiota composition is not entirely understood. Methods: We developed a mouse model of AECOPD by cigarette smoke exposure and sequential infection with influenza H1N1 virus and non-typeable Haemophilus influenzae (NTHi). Viral and bacterial titer was determined using MDCK cells and chocolate agar plates, respectively. The levels of cytokines, adhesion molecules, and inflammatory cells in the lungs were measured using Bio-Plex and flow cytometry assays. Gut microbiota was analyzed using 16S rRNA gene sequencing. Correlations between cytokines and gut microbiota were determined using Spearman’s rank correlation coefficient test. Results: Coinfection with H1N1 and NTHi resulted in more severe lung injury, higher mortality, declined lung function in COPD mice. H1N1 enhanced NTHi growth in the lungs, but NTHi had no effect on H1N1. In addition, coinfection increased the levels of cytokines and adhesion molecules, as well as immune cells including total and M1 macrophages, neutrophils, monocytes, NK cells, and CD4+ T cells. In contrast, alveolar macrophages were depleted. Furthermore, coinfection caused a decline in the diversity of gut bacteria. Muribaculaceae, Lactobacillus, Akkermansia, Lachnospiraceae, and Rikenella were further found to be negatively correlated with cytokine levels, whereas Bacteroides was positively correlated. Conclusion: Coinfection with H1N1 and NTHi causes a deterioration in COPD mice due to increased lung inflammation, which is correlated with dysbiosis of the gut microbiota.